Increased Toxoplasma gondii Intracellular Proliferation in Human Extravillous Trophoblast Cells (HTR8/SVneo Line) Is Sequentially Triggered by MIF, ERK1/2, and COX-2 - Milian, Iliana Claudia Balga; Silva, Rafaela José; Manzan-Martins, Camilla; Barbosa, Bellisa Freitas; Guirelli, Pamela Mendonça; Ribeiro, Mayara; de Oliveira Gomes, Angelica; Ietta, Francesca; Mineo, José Roberto; Silva Franco, Priscila; Ferro, Eloisa Amália Vieira (Frontiers in Microbiology, 2019)
Macrophage migration inhibitory factor (MIF) is a potent pro-inflammatory cytokine, which mediates the regulation of diverse cellular functions. It is produced by extravillous trophoblastic cells and has been found to be involved in the pathogenesis of diseases caused by some protozoa, including Toxoplasma gondii. Previous studies demonstrated the ability of T. gondii to take advantage of MIF action in human trophoblast cells. However, MIF action in T. gondii-infected extravillous trophoblastic cells (HTR8/SVneo cell line) has not been fully investigated. The present study aimed to investigate the role of MIF in T. gondii-infected HTR8/SVneo cells and verify the intracellular signaling pathways triggered by this cytokine. We found that T. gondii increased MIF production by HTR8/SVneo cells, and by contrast, MIF inhibition, by ISO-1, led to a significant decrease in T. gondii proliferation and CD74 expression in HTR8/SVneo cells. Moreover, in infected HTR8/SVneo cells, the addition of recombinant MIF (rMIF) increased CD44 co-receptor expression, ERK1/2 phosphorylation, COX-2 expression, and IL-8 production, which favored T. gondii proliferation. Our findings indicate that T. gondii can use MIF to modulate important factors in HTR8/SVneo cells, being a possible explanation for the higher susceptibility of extravillous trophoblast cells than other trophoblast cell populations.